Adolescents and substance use the handbook for professionals working with young people - James, Philip; Kearns, Caitríona; Campbell, Ann; Smyth, Bobby P. (Radcliffe Publishing, 2014)
This highly practical manual presents an ideal introduction to adolescent substance use. It offers invaluable guidance for all professionals involved with adolescents including social workers, health and social care professionals, youth workers, family support workers, teachers, counsellors, mental health teams, A&E staff, police and probation officers. The approach these practitioners take in dealing with the problem has considerable influence over outcomes. It succinctly covers a wealth of information on key matters such as counselling, treatment options, motives for substance abuse, sexual and mental health, policy development, ethical and legal considerations, and the important role of the family. Adolescents and Substance Use provides a user-friendly foundation for effective, evidence-based practice.--Publisher